The Qur'an and the just society - Harvey, Ramon (Edinburgh University Press Ltd, 2018)
Utilising a pioneering theological and hermeneutic framework adapted from both classical Muslim literature and contemporary academic studies of the Qur'an, Ramon Harvey explores the underlying principles of its system of social justice.